Importance of the Motivational Climate in Goal, Enjoyment, and the Causes of Success in Handball Players - Granero-Gallegos, Antonio; Gómez-López, Manuel; Rodríguez-Suárez, Nuria; Abraldes, J. Arturo; Alesi, Marianna; Bianco, Antonino (Frontiers in Psychology, 2017)
This study examines the effects of the motivational climate created by the coach and perceived by young athletes on their goal orientations and beliefs about success and satisfaction according to the achievement goal theory. The study participants were 159 young handball players. Athletes administered a battery composed of tests to measure the above-mentioned motivational constructs. Results showed that a perceived mastery-oriented motivational climate was positively related to a task-centered goal orientation, enjoyment, and a belief that success may be achieved through effort. In contrast, a perceived performance-orientated training climate was linked to an ego-centered goal orientation, boredom or lack of enthusiasm, and a belief that the routes of success in this sport are the abilities and the use of deception techniques. On the whole, this study underlines the educational role of the coach in adolescents and young athletes. Specifically, the coach's socializing role influences both handball player's commitment and positive motivational profile as well as sport performance.